Label-free proteomic analysis reveals freshness-related proteins in sea bass (Lateolabrax japonicus) fillets stored on ice. (1st February 2022) - Xiang, Yue; Sun, Chengfeng; Zhao, Yongqiang; Li, Laihao; Yang, Xianqing; Wu, Yanyan; Chen, Shengjun; Wei, Ya; Li, Chunsheng; Wang, Yueqi
Abstract: The advantages of epigallocatechin gallate incorporated in agar oligosaccharide treatment during post-mortem storage on ice for maintaining the quality and proteome stability of sea bass muscle was investigated using hardness, total volatile basic nitrogen, total viable counts, protein biochemical properties and label-free proteomic analysis. The results indicated that hardness value and sulfhydryl content of EGCG–AO-treated fish muscle were much higher than those of the samples immersed in sterile water. The total volatile basic nitrogen, total viable counts, and carbonyl content increased to 165.65%, 18.93%, and 42.37%, respectively after 8 days of storage. Proteomic analysis of muscle samples from control fillets on days 0 (CK0) and 8 (CK8), and EGCG–AO-treated fillets on day 8 (T8) revealed 708 different abundant proteins (DAPs). DAPs in CK8 vs. CK0 fillets were mainly structural proteins, metabolic enzymes, and proteins involved in protein turnover, and were closely related with freshness properties. Muscles from fillets in T8 showed delayed degradation of structural proteins, lower abundance of calpain and carbohydrate metabolic enzymes, and maintained higher levels of transcription and translation to maintain quality. Thus, EGCG–AO treatment is a possible method for maintaining freshness of sea bass fillets. Several DAPs are potential proteomic markers for monitoring fillet freshness. Highlights: We evaluated the effects of EGCG + AO on fish fillet quality. EGCG + AO delays protein degradation and suppresses metabolism. Potential markers for monitoring freshness during ice storage were identified.